2019
DOI: 10.1111/jfb.13888
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive behaviour and concurrent sound production of Gulf grouper Mycteroperca jordani (Epinephelidae) at a spawning aggregation site

Abstract: The reproductive and acoustic behaviours of Gulf grouper Mycteroperca jordani were studied at a spawning aggregation site in the southern Gulf of California, México. In May 2015–2017, divers located and surveyed a spawning aggregation site within Cabo Pulmo National Park. Adult M. jordani conformed to a lek mating system in which large males formed territories over sand adjacent to a rocky reef that were spatially segregated from smaller females outside of courtship and spawning periods. Females moved into mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 96 publications
0
13
0
1
Order By: Relevance
“…Results from this study indicated there was no significant difference in hourly residency of fish based on lunar phase as fish were detected during all hours of night across all lunar phases. GSB may be comparable to grouper and snapper species in the Gulf of California that spawn across variable lunar phases, with the large Gulf grouper (Mycteroperca jordani) and leopard grouper (M. rosacea) showing no significant differences in spawning across lunar phases (Erisman et al 2007;Rowell et al 2019). It is possible that abundance and densities of GSB at Catalina are too low to support consistent spawning aggregations, regardless of lunar phase, temperature, or location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from this study indicated there was no significant difference in hourly residency of fish based on lunar phase as fish were detected during all hours of night across all lunar phases. GSB may be comparable to grouper and snapper species in the Gulf of California that spawn across variable lunar phases, with the large Gulf grouper (Mycteroperca jordani) and leopard grouper (M. rosacea) showing no significant differences in spawning across lunar phases (Erisman et al 2007;Rowell et al 2019). It is possible that abundance and densities of GSB at Catalina are too low to support consistent spawning aggregations, regardless of lunar phase, temperature, or location.…”
Section: Discussionmentioning
confidence: 99%
“…Although sex of tagged GSB was not assessed in this study nor could it be assessed through visual observation, fish with the shortest distance traveled during the spawning season may have been gravid females that spent most of their time close to spawning aggregation sites to conserve energy for reproduction (i.e., egg production [ Table 2]). However, male gulf groupers, a species of comparable size and range, form leks with dominant males maintaining territories during aggregation spawning while females swim long distances in search of mates (Rowell et al 2019). Although such leks may not seem beneficial for non-resource-based mating systems like broadcast spawning in aggregations (Borgia et al 1979), GSB may exhibit this behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The females kept in captivity had abdomens that remained distended throughout the experiment, and no eggs were observed in the tank. Since no spawning was detected in captivity it remains unknown if any sounds are produced by Red Hind during gamete release, although this has been demonstrated for the Gulf Grouper (Rowell et al 2019). In Atractoscion nobilis (White Seabass) there is also an association between sound production (drumrolls and thuds) and spawning (Aalbers and (Lobel 1992, Mann andLobel 1995).…”
Section: Comparison Of Call Typesmentioning
confidence: 99%
“…The CAS produced by Red Hind are of low frequency (50-450 Hz) and occur during the spawning aggregation, associated with reproductive behaviors and male displays towards males and gravid females (Mann et al 2010). Visual observations, coupled with passive acoustic recordings have been used to categorize sounds associated with behavioral displays by Nassau Grouper (Schärer et al 2012a), Mycteroperca jordani (Gulf Grouper; Rowell et al 2019), Mycteroperca bonaci (Black Grouper;Schärer et al 2014), Mycteroperca venenosa (Yel-lowfin Grouper;Schärer et al 2012b), Epinephelus polyphekadion (Camouflage Grouper;Jublier et al 2020), Epinephelus marginatus (Dusky Grouper;Bertucci et al 2015) and Epinephelus morio (Red Grouper;Nelson et al 2011), with the latter using lek-like systems of reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…This type of information, which includes understanding the phenology of reproducing species using this pass, is thus essential for management actions that will secure the long-term health and persistence of local grouper populations (Mourier et al, 2019). Within the Epinephelidae, acoustic signals have been associated with courtship behaviour and are likely to be related to the spawning activity of many species, including Epinephelus guttatus (the red hind) (Mann, Locascio, Schärer, Nemeth, & Appeldoorn, 2010), Epinephelus itajara (the goliath grouper) (Mann, Locascio, Coleman, & Koenig, 2009), Epinephelus marginatus (the dusky grouper) (Bertucci, Lejeune, Payrot, & Parmentier, 2015), Epinephelus morio (the red grouper) (Nelson, Koenig, Coleman, & Mann, 2011), Epinephelus striatus (the Nassau grouper) , Mycteroperca bonaci (the black grouper) (Schärer, Nemeth, Rowell, & Appeldoorn, 2014), Mycteroperca jordani (the Gulf grouper) (Rowell, Aburto-Oropeza, Cota-Nieto, Steele, & Erisman, 2018), and Mycteroperca venenosa (the yellowfin grouper) . To our knowledge, however, vocalizations have not been assessed for any Pacific grouper species to date, including the camouflage grouper.…”
Section: Introductionmentioning
confidence: 99%